A common framework for integrated and continuous biomanufacturing. Issue 4 (1st March 2021) - Coffman, Jonathan; Brower, Mark; Connell‐Crowley, Lisa; Deldari, Sevda; Farid, Suzanne S.; Horowski, Brian; Patil, Ujwal; Pollard, David; Qadan, Maen; Rose, Steven; Schaefer, Eugene; Shultz, Joseph
Abstract: There is a growing application of integrated and continuous bioprocessing (ICB) for manufacturing recombinant protein therapeutics produced from mammalian cells. At first glance, the newly evolved ICB has created a vast diversity of platforms. A closer inspection reveals convergent evolution: nearly all of the major ICB methods have a common framework that could allow manufacturing across a global ecosystem of manufacturers using simple, yet effective, equipment designs. The framework is capable of supporting the manufacturing of most major biopharmaceutical ICB and legacy processes without major changes in the regulatory license. This article reviews the ICB that are being used, or are soon to be used, in a GMP manufacturing setting for recombinant protein production from mammalian cells. The adaptation of the various ICB modes to the common ICB framework will be discussed, along with the pros and cons of such adaptation. The equipment used in the common framework is generally described. This review is presented in sufficient detail to enable discussions of IBC implementation strategy in biopharmaceutical companies and contract manufacturers, and to provide a road map for vendors equipment design. An example plant built on the common framework will be discussed. The flexibility of the plant is demonstrated with batches as small as 0.5 kg or as large as 500 kg. The yearly output of the plant is as much as 8 tons. Abstract : This article reviews the integrated and continuous bioprocesses (ICB) that are being used, or are soon to be used, in a GMP manufacturing setting for recombinant protein production from mammalian cells, and proposes a common framework. A common framework plant is described that can produce batches as small as 0.5 kg or as large as 500 kg. The yearly output of the plant is as much as 8 tons.